The Influence of Nutritional Anemia Education Media on the Knowledge Level of Adolescents in Anemia Prevention Literature Review - Rani Safitri; Mohammed Saifulaman Mohammed Said; Tut Rayani Aksohini Wijayanti (Universitas STRADA Indonesia, 2024)
Background: The increasing need for nutrients during adolescence due to growth and menstruation experienced by young women causes young women to be susceptible to anaemia. Anaemia is a condition where the haemoglobin level in the blood is less than the normal value. One of the factors causing anaemia is the lack of knowledge among teenagers about anaemia. Many types of media, both visual and audiovisual, can be used to convey education about anaemia. Purpose: To determine the effectiveness of nutrition education media in increasing teenagers' knowledge of preventing anaemia. Methods: This research uses a literature review design. A literature review study is a method used to collect data or sources related to a particular topic, which can be obtained from various sources such as research articles. Results: From the reviewed articles, five showed an increase in teenagers' average knowledge score after being educated using visual media. There is 1 article that shows an increase in teenagers' average knowledge score after being educated using audiovisual media. Three articles showed an increase in teenagers' average knowledge score after being educated using visual and audiovisual media. Conclusion: Visual and audiovisual media are effective when used together to help increase teenagers' nutrition knowledge and provide nutritional education about anaemia. When delivering nutritional education about anaemia to teenagers, using visual and audiovisual media simultaneously is recommended to get effective results.